On-demand coupling of electrically generated excitons with surface plasmons via voltage-controlled emission zone position - Zakharko, Yuriy; Held, Martin; Sadafi, Fabrizio-Zagros; Gannott, Florentina; Mahdavi, Ali; Peschel, Ulf; Taylor, Robin N. Klupp; Zaumseil, Jana (ACS photonics, 2016)
The ability to confine and manipulate light below the diffraction limit is a major goal of future multifunctional optoelectronic/plasmonic systems. Here, we demonstrate the design and realization of a tunable and localized electrical source of excitons coupled to surface plasmons based on a polymer light-emitting field-effect transistor (LEFET). Gold nanorods that are integrated into the channel support localized surface plasmons and serve as nanoantennas for enhanced electroluminescence. By precise spatial control of the near-infrared emission zone in the LEFET via the applied voltages the near-field coupling between electrically generated excitons and the nanorods can be turned on or off as visualized by a change of electroluminescence intensity. Numerical calculations and spectroscopic measurements corroborate significant local electroluminescence enhancement due to the high local density of photonic states in the vicinity of the gold nanorods. Importantly, the integration of plasmonic nanostructures hardly influences the electrical performance of the LEFETs, thus, highlighting their mutual compatibility in novel active plasmonic devices.
Gesehen am 01.10.2021